2005
DOI: 10.1111/j.1360-0443.2005.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of smoking reduction: an update

Abstract: Aim To update conclusions of a previous review of smoking reduction on the extent to which (1) smokers spontaneously reduce their smoking, (2) smokers who try to quit and fail return to smoking less, (3) smokers can substantially reduce and maintain reductions via pharmacological and behavioral treatments and (4) smokers compensate when they reduce.Method Qualitative systematic review. Data sources Systematic computer searches and other methods. Study selectionPublished and unpublished studies of smokers not t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
2
10

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(136 citation statements)
references
References 85 publications
5
119
2
10
Order By: Relevance
“…We provide novel information regarding ST reduction among ST users not interested in quitting (i.e., not having an established quit date within the next 90 days). This population is distinctly different from a population of ST users actively trying to achieve tobacco abstinence through reduction, frequently referred to "gradual cessation" (Hughes & Carpenter, 2005). Studies in smokers suggest that reduction programs increase the percentage of smokers willing to participate (Glasgow et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…We provide novel information regarding ST reduction among ST users not interested in quitting (i.e., not having an established quit date within the next 90 days). This population is distinctly different from a population of ST users actively trying to achieve tobacco abstinence through reduction, frequently referred to "gradual cessation" (Hughes & Carpenter, 2005). Studies in smokers suggest that reduction programs increase the percentage of smokers willing to participate (Glasgow et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…This may be because when smokers reduce their smoking (a) their selfefficacy about quitting increases, (b) they learn skills to combat urges and high-risk-for-relapse situations, (c) conditioned cravings to cues to smoke are disrupted, and (d) their level of nicotine dependence decreases. Many prior studies have shown that nicotine replacement therapies (NRTs) can aid in this reduction (Hughes & Carpenter, 2005). In fact, in Europe, several countries have approved NRT for reduction in smokers who plan to quit at a later date (in the United States, NRT is indicated only for those who are currently making a quit attempt).…”
Section: Introductionmentioning
confidence: 99%
“…Other smoking reduction studies have shown greater reductions in smoking with the use of medicinal nicotine compared with placebo or no-treatment groups, but again no dramatic reductions in exposure biomarkers were observed as a result of using these treatments (see Hughes & Carpenter, 2005, for review). If smokers in these studies were compensating for the reduced nicotine concentrations that accompanied cigarette reductions, the observed compensatory smoking behavior may have resulted from insufficient nicotine replacement.…”
Section: Methods and Mechanismsmentioning
confidence: 99%
“…To date, the best method to achieve this outcome is abstinence from all tobacco products. Studies have shown that cigarette reduction attained through the use of nicotine replacement agents and bupropion SR results in 5%-36% (M=11%) point-prevalence abstinence rates among smokers who, at the time of enrollment, had no immediate quit plans (Hughes & Carpenter, 2005). A few studies have directly compared smoking reduction with advice to quit or no treatment.…”
Section: Ultimate Outcomementioning
confidence: 99%